The system design of the peat-based microbial fuel cell as a new renewable energy source: The potential and limitations - Erensoy, Ahmet; Mulayim, Sefa; Orhan, Ayhan; Cek, Nurettin; Tuna, Aysun; Ak, Namik (Elsevier, 2022)
The microbial fuel cell (MFC) is considered as a renewable, non-toxic, reliable, clean, efficient, and also an alternative source for bioenergy. It provides numerous opportunities to improve sustainable applications in various sites, ranging from industrial to home. The low power output of microbial fuel cells is one of the important factors that hinder their commercialization. Power outputs must be improved to contribute to the commercialization of MFCs. In this study, organic peat material was used as a substrate for a double chamber MFC. In addition, since Clostridium bacteria were detected in the organic peat material, an additional bacterial strain was not used. In this MFC application, where graphite is used as both anode and cathode electrodes, 1 mol/L NaOH solution was employed as the cathode chamber solution. This peat-based MFC provided the highest electrical power density of 438.116 mW/m(2). The most important limiting factor of the peat-based MFC was the spreading of the NaOH solution throughout the cell due to the rupture of the proton exchange membrane after 9 h of operation. (C) 2022 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Alexandria University This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/ 4.0/).
Keywords: Peat; Microbial fuel cell; Bioelectricity; Microorganism